Availability analysis of safety-critical systems of nuclear power plant using ordinary differential equations and reachability graph - Jyotish N.K.; Singh L.K.; Kumar C. (My University, 2025)
With the growing advancement and demand for technology, computer-based systems (CBS) have become an integral part of human life. Numerous CBSs are safety and mission-critical in nature, and are employed in various industries, including nuclear power plant (NPP), locomotive control, avionics, medical automation, etc. Safety-critical systems (SCS) are one such CBS that are vital to control and maintain the infrastructure of NPP. This paper presents an inventive technique to assess the performance metric availability of SCSs. A Petri net (PN) models such systems, which feature multiple processing nodes interacting with one another. PN models are useful for generating the reachability graph. This article uses reachability graph to derive a collection of ordinary differential equations (ODEs), whose solution can be applied for assessing the availability of the system. Conventional methods like Markovian chains, Reliability Block diagrams (RBDs), Fault Tree Analyses (FTAs), and Flow Networks fail to cover the systems' behaviors and structures properties, as well as the lack of failure data, and the diversity of possible failures. The suggested technique has been applied to Digital Feed Water Control System (DFWCS) of NPP, which consider the failure, maintenance and repairment of the main-steam safety valves. We achieved 99.20% accuracy of availability measurement, proving the efficacy of methodology. © 2023 Elsevier Ltd